2021
DOI: 10.1016/j.psj.2021.101172
|View full text |Cite
|
Sign up to set email alerts
|

Use of lemongrass essential oil as a feed additive in quail's nutrition: its effect on growth, carcass, blood biochemistry, antioxidant and immunological indices, digestive enzymes and intestinal microbiota

Abstract: The present study was designed to assess the impact of dietary supplementation of lemongrass essential oil ( LGEO ) on growth performance, carcass traits, liver and kidney function, immunity, antioxidant indices and caecal microbiota of growing quail. A total of 200 Japanese quails at 1-week-old were haphazardly allotted to 5 groups of 40 chicks in five replicates (8 per replicate). The first group was the control group, while LGEO was added at levels of 150, 300, 450, and 600 mg/kg diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 45 publications
8
73
0
1
Order By: Relevance
“…Widespread Japanese quail breeding in developing countries may help overcome the current gap in meat supply ( Minvielle 2004 ; Alagawany et al, 2021a ; Reda et al, 2021 ). Quails are economically important as a source of meat and eggs, but quail production has not yet reached its full potential in the poultry industry ( Genchev et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Widespread Japanese quail breeding in developing countries may help overcome the current gap in meat supply ( Minvielle 2004 ; Alagawany et al, 2021a ; Reda et al, 2021 ). Quails are economically important as a source of meat and eggs, but quail production has not yet reached its full potential in the poultry industry ( Genchev et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, dietary manipulation with innovative feed supplements, such as medicinal plant and its derivatives, are among the common advanced strategies [5,[24][25][26]. Medicinal plants are re ected a cornerstone of medicine since earliest times, and have been employed as promoters of antioxidant capacity, immunity and growth in animals [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kaewamatawong et al [33] studied the acute to subchronic toxicity of LST in mice and found that LST signi cantly decreased the triglyceride values but did not induce any toxicological effects in the acute and subchronic term. The presence of anti-hypertensive compounds such as avonoids and alkaloids present in LST could be responsible to reduce serum triglycerides and LDL-C and enhancing the HDL-C levels and thus avoiding cardiovascular ailment [24]. Further studies should be conducted to validate the underlined mechanism of LST as an anti-hypertensive agent for drug treatments in poultry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EO components with different functional groups exhibit different levels of antimicrobial potential where phenols and aldehydes have the highest activities while esters and hydrocarbons have the least [38]. However, the antimicrobial activity of lemongrass is extensively attributed to the citral (aldehyde) present in its oil [26,39,40]. It is suggested low concentration of LEO inhibits microbial growth and development (bacteriostatic, fungistatic, and virustatic) while higher concentration renders irreversible destruction leading to microbial death (bactericidal, fungicidal, and virucidal) [41,42].…”
Section: Antimicrobial Potentialmentioning
confidence: 99%